1988
DOI: 10.1055/s-2007-1020079
|View full text |Cite
|
Sign up to set email alerts
|

Supraventricular Tachyarrhythmias After Coronary Bypass Surgery - A Double Blind Randomized Trial of Prophylactic Low Dose Propranolol

Abstract: In the present study 75 patients were double blind randomized either to receive 10 mg propranolol orally 4 times a day (35 patients) or a placebo (40 patients). Episodes of clinically important supraventricular tachyarrhythmias were recorded in the first 4 postoperative days. They appeared in 5 of 35 patients receiving propranolol and in 5 of 40 patients receiving placebo (no statistically significant difference). In conclusion this study indicates the need for further evaluation to clarify if low-dose propran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Most of the trials excluded patients with severely decreased left ventricular function, and the reported values of mean ejection fraction of the patients enrolled were in the range of 43% to 68%. 19,46 The percentage of patients with history of previous myocardial infarction varied from 26% to 85%. 25,47 The prevalence of use of preoperative ␤-blockers varied, because some trials were designed to evaluate the role of ␤-blocker withdrawal phenomena, 23 whereas others excluded patients not taking ␤-blockers preoperatively.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the trials excluded patients with severely decreased left ventricular function, and the reported values of mean ejection fraction of the patients enrolled were in the range of 43% to 68%. 19,46 The percentage of patients with history of previous myocardial infarction varied from 26% to 85%. 25,47 The prevalence of use of preoperative ␤-blockers varied, because some trials were designed to evaluate the role of ␤-blocker withdrawal phenomena, 23 whereas others excluded patients not taking ␤-blockers preoperatively.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…11,24,25 In trials published after 1995, the proportion of patients undergoing ␤-blocker therapy preoperatively was 61% to 80%. 12,13,33 The timing of initiation of study treatment varied between the trials, starting before, 9,10,18,19,25,38,39,41,43,45,48,49 during, 44 or after 6,11-17,20 -24,26 surgery. In 2 trials, 16,31 the intervention drug was administered at the end of ICU stay.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…The efficacy of pharmacologic prophylaxis in reducing the incidence of AF has been investigated in several studies, and different studies have addressed the issue of preventing AF after CABG [Martinussen 1988;Kerstein 2004;Bradley 2005;Imren 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Morcover, some of the beta-blocker trials showed conflicting results (8,9,30). In one study with a high douse of sotalol, there was a marked reduction in supraventricular tachyarrhythmias (22).The present report confirms the results of Suttorp ct al (23) and extends it to an unselected group of patients showing that a low dose of sotalol is sufficient to prevent supraventricular tachyarrhythmias in a large proportion of patients.…”
Section: Incidence and Predictors Of Supraventricular Tachyarrhythmiasmentioning
confidence: 98%
“…It has been suggested that this complication could be reduced by modern cardioprotection during general anesthesia (3,4). Several antiarrhythmic drugs have been used to treat or prevent these supraventricular arrhythmias such as digoxine (6,7), beta-adrenergic blocking drugs (8)(9)(10), calcium antagonists (11), quinidine (12), propafenone (13), flecainide (14), procainamide (15), amiodarone (16,17), and magnesium (18). Whereas there are conflicting results from different studies for most of these drugs, this is not true for beta-blocking drugs.…”
mentioning
confidence: 99%